0
$\begingroup$

The question is:

Let $Y_1,....,Y_n$ be independent random variables each with the distribution $N\left ( \mu ,\sigma ^2 \right )$.

Let:

$\overline{Y} = \frac{1}{n}\sum_{i=1}^{n}Y_i$

$S^2 = \frac{1}{n-1}\sum_{i=1}^{n}\left ( Y_i - \overline{Y} \right )^2$

Show that: $S^2 = \frac{1}{n-1}\left [ \sum_{i=1}^{n}\left ( Y_i-\mu \right )^2 - n\left ( \overline{Y}-\mu \right )^2 \right ]$

This is as far as I've being able to get:

$S^2 = \frac{1}{n-1}\sum_{i=1}^{n}\left ( Y_i - \overline{Y} \right )^2$

$= \frac{1}{n-1}\left [ \sum_{i=1}^{n}\left ( Y_i-\overline{Y} \right )\sum_{j=1}^{n}\left ( Y_j -\overline{Y} \right ) \right ]$

I intend the first double summation to be for when $i=j$ and the second for when $i\neq j$...

$= \frac{1}{n-1}\sum_{i=1}^{n}\sum_{j=1}^{n}\left ( Y_i-\overline{Y} \right ) \left ( Y_j-\overline{Y} \right )+\frac{1}{n-1}\sum_{i=1}^{n}\sum_{j=1}^{n}\left ( Y_i-\overline{Y} \right ) \left ( Y_j-\overline{Y} \right )$

$= \frac{1}{n-1}\sum_{i=1}^{n}\left ( Y_i-\overline{Y} \right )^2 +\frac{1}{n-1}\sum_{i=1}^{n}\sum_{j=1}^{n}\left ( Y_i-\overline{Y} \right ) \left ( Y_j-\overline{Y} \right )$

Would anyone know how to finish the question off from here or any mistakes I've made thus far?

The question is exercise 1.4 from this textbook.

Thank you.

$\endgroup$
  • 1
    $\begingroup$ This is an FAQ, mainly because this question is usually stated exactly the same way each time--but it's in mathematical notation, which is difficult to search! I am confident there are at least 20 exact duplicates here and would therefore be grateful to anyone who could locate one. $\endgroup$ – whuber Jul 12 '17 at 13:29
  • 2
    $\begingroup$ BTW, this question has nothing to do with independence, normality, or even random variables: it's a purely algebraic result. Demonstrating it is merely an exercise in using summation notation. If that's not clear, write it out explicitly for the case $n=2$: the pattern should become apparent. $\endgroup$ – whuber Jul 12 '17 at 13:43
2
$\begingroup$

As whuber points out, this is simply an exercise in algebra that has nothing to do with random variables or normality; all that is needed is the definition that $\bar{Y} \triangleq \frac 1n \sum_{i=1}^n Y_i$ which can be manipulated into $$0 = \left(\sum_{i=1}^n Y_i\right) - n\bar{Y} = \sum_{i=1}^n (Y_i -\bar{Y}) .$$ We have that \begin{align} \require{cancel} \sum_{i=1}^n (Y_i-\mu)^2 &= \sum_{i=1}^n (Y_i-\bar{Y} + \bar{Y} - \mu)^2\\ &= \sum_{i=1}^n \left[(Y_i-\bar{Y})^2 + (\bar{Y}-\mu)^2 + 2(Y_i-\bar{Y})(\bar{Y}-\mu)\right]\\ &= \sum_{i=1}^n (Y_i-\bar{Y})^2 + \sum_{i=1}^n (\bar{Y}-\mu)^2 + \sum_{i=1}^n 2(Y_i-\bar{Y})(\bar{Y}-\mu)\\ &= \sum_{i=1}^n (Y_i-\bar{Y})^2 + n\cdot (\bar{Y}-\mu)^2 + 2(\bar{Y}-\mu)\sum_{i=1}^n (Y_i-\bar{Y})\\ &= \sum_{i=1}^n (Y_i-\bar{Y})^2 + n\cdot (\bar{Y}-\mu)^2 +2 (\bar{Y}-\mu)\cancelto{0}{\sum_{i=1}^n (Y_i-\bar{Y})}\\ &= \sum_{i=1}^n (Y_i-\bar{Y})^2 + n\cdot (\bar{Y}-\mu)^2\\ &\Downarrow\\ \frac{1}{n-1}\sum_{i=1}^n (Y_i-\bar{Y})^2 &= \frac{1}{n-1}\left[\sum_{i=1}^n (Y_i-\mu)^2 - n\cdot (\bar{Y}-\mu)^2\right]. \end{align} Note that the proof works for all choices of number $\mu$; there is no requirement that $\mu$ equal the expected value of anything.

| cite | improve this answer | |
$\endgroup$
  • $\begingroup$ Thank you very much! However, how did you know to start off with (Yi−μ)? Is there any other way to obtain μ from the original equation for S^2? $\endgroup$ – Tejay Lovelock Jul 12 '17 at 23:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.